الخصائص السوسيوديموغرافية للولادة القيصرية في الجزائر - عبد العزيز,سيهام (University of Eloued جامعة الوادي, 2023)
تهدف هذه الدراسة الى تحديد بعض العوامل السوسيوديموغرافية التي تخص الولادة القيصرية في الجزائر وتم اتباع المنهج الوصفي التحليلي، بناءا على قاعدة بيانات المسح العنقودي متعدد المؤشرات في الجزائر سنة 2019 وقد تم التوصل إلى النتائج التالية: عرفت الجزائر ارتفاعا ملحوظا في معدل الولادات القيصرية حيث قدرت ب 25% حسب المسح العنقودي ، كما تميزت الفئة العمرية الثالثة بزيادة في نسبة إجراء العملية القيصرية وذلك لأن هذا السن هو الفترة الزمنية النشطة للزواج والحمل أما بالنسبة للفئة العمرية الرابعة فإن سبب زيـادة نـسبة إجـراء العملية القيصرية هو بسبب زيادة المخاطر والمضاعفات للحمل والولادة في هذا السن ،بالإضافة كلما ارتفع المستو ى التعلیمي للسـیدات كلمـا زاد اللجوء للعملیة القیصریة من اجل الوضع. وفي ضوء هذه النتائج تقترح الدراسة العملعلى تحسين تكوين المشرفين على الولادة بشكل افضل للتقليل من الولادات القيصرية إلا تلك المتعلقة بضرورة طبية، من خلال تقديم تدابير بسيطة مثل التواصل الجيد والدعم وتعاطف العاملين في مجال الرعاية الصحية . الكلمات المفتاحية: الولادة القيصرية؛ الامهات؛ عوامل اجتماعية؛ عوامل ديموغرافية؛ المسح العنقودي متعدد المؤشرات. Abstract: This study aims to identify some sociodemographic factors related to caesarean section in Algeria. The descriptive analytical approach was followed, based on the database of the Multiple Indicator Cluster Survey in Algeria in 2019. The following results were reached: Algeria has witnessed a significant increase in the rate of caesarean section, where It was estimated at 25% according to the mics6 cluster survey. The third age group was also characterized by an increase in the rate of caesarean section, because this age is the active time period for marriage and pregnancy. As for the fourth age group, the reason for the increase in the rate of caesarean section is due to the increased risks and complications of pregnancy and childbirth in This age, in addition to the higher the educational level of women, the more resort to caesarean section for delivery. In the light of these results, the study proposes to work on improving the training of birth attendants better to reduce cesarean deliveries except those related to medical necessity, by providing simple measures such as good communication, support and sympathy of health care workers.
Keywords: الولادة القيصرية; الامهات; عوامل اجتماعية; عوامل ديموغرافية; المسح العنقودي متعدد المؤشرات; Caesarean section; Mothers; Social factors; Demographic factors; Multiple Indicator Cluster Survey